TiO2@C core-shell nanoparticles formed by polymeric nano-encapsulation - Vasei, Mitra; Das, Paramita; Cherfouth, Hayet; Marsan, Benoît; Claverie, Jerome P. (Frontiers in Chemistry, 2014)
TiO2 semiconducting nanoparticles are known to be photocatalysts of moderate activity due to their high band-gap and high rate of electron-hole recombination. The formation of a shell of carbon around the core of TiO2, i.e. the formation of TiO2@C nanoparticles, is believed to partly alleviate these problems. It is usually achieved by a hydrothermal treatment in a presence of a sugar derivative. We present here a novel method for the formation of highly uniform C shell around TiO2 nanoparticles. For this purpose, TiO2 nanoparticles were dispersed in water using an oligomeric dispersant prepared by Reversible Addition-Fragmentation chain Transfer (RAFT) polymerization. Then the nanoparticles were engaged into an emulsion polymerization of acrylonitrile, resulting in the formation of a shell of polyacrylonitrile (PAN) around each TiO2 nanoparticles. Upon pyrolisis, the PAN was transformed into carbon, resulting in the formation of TiO2@C nanoparticles. The structure of the resulting particles was elucidated by X-Ray diffraction, FTIR, UV-VIS and Raman spectroscopy as well as TEM microscopy. Preliminary results about the use of the TiO2@C particles as photocatalysts for the splitting of water are presented. They indicate that the presence of the C shell is responsible for a significant enhancement of the photocurrent.